El espectáculo revolucionario: El teatro cubano de la década de los sesenta - Ford, Katherine (Latin American Theatre Review, 2005)
This essay examines how three plays written in Cuba during the sixties question the official Revolutionary discourse. By representing the instability and violence that emerge from this imposition, they reveal the repetition that underlies the revolutionary moment. José Triana’s La noche de los asesinos, Virgilio Piñera’s Una caja de zapatos vacía and Antón Arrufat’s Los siete contra Tebas approach the idea of violence and repetition through the motif of revolution as both a violent break with the past and, ironically, a return to this very past through an inability to break free from the circularity of history. (KF)